Formation of a destructive layer in special rubbers depending on CO2-laser processing modes - Sidorov, Dmitro; Kozik, Denys; Kazak, Iryna; Shylovych, Tetiana; Pribyliev, Yurii (Eastern-European Journal of Enterprise Technologies, 2025)
Special rubbers proceeding by laser engraving is the investigation object. Rubber products quality improvement was solving by means of laser engraving, which allows to achieve a high level of details, to get a complex geometry and sustainable quality having a minimum of the tool worn out. Experimental measurements of destructive layer depth inside different samples of rubber in dependence on the modes of CO2-laser processing were conducted. Rubber engraving proceeding by a wavelength of 10.6 μm CO2-laser was considered in the pulse mode series to provide the cutting edge correct geometry keeping fixed conditions of beam movement speed and acceleration. Concerted experimental results (rubbers AERO Laserrubber, OLIO Laserrubber, TEMPO Laserrubber, CLASSICO Laserrubber and ECO Laserrubber) revealed a sustainable increasing the depth of the destructive layer on average by (1.0 ... 1.2) μm every 5 W along with increasing of CO2-laser power in the range of (30 ... 55) W. Stabilization or slight fluctuations of the destructive layer depth were stated when power supplied exceeded of 60 W. Obtained graphs show a high degree coincidence with analytical model and confirm the feasibility of laser engraving appliance exactly within the range of (35 ... 50) W to provide a precise and clean processing of high-quality rubber products